ANALISIS PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN PERUSAHAAN (Studi Pada Perusahaan Sektor Pertambangan yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2022) - Hanstiene Dwiaz Wiandani (Jurnal Studi Akuntansi Pajak Keuangan, 2024)
The purpose of this study is to study the effect of the independent variables Corporate Social Responsibility (CSR) and company size on the dependent variable of financial performance in companies listed on the IDX for the 2020-2022 mining sector. This study uses a total sample of 20 companies. Sampling used is subjective sampling method. The research analysis uses a statistical approach, namely the panel data regression method. On the basis of the results of the analysis, the first and second conjectures reveal that the CSR variable and company size have a positive influence on financial performance. The third conjecture reveals that the variables CSR and company size together have an influence on financial performance.